Kiat jitu tes potensi akademik. Persiapan masuk perguruan tinggi dan masuk kerja - [Tidak Terdaftar] (Andi Offset, 2006)
Kiat jitu tes potensi akademik. Persiapan masuk perguruan tinggi dan masuk kerja